2012
DOI: 10.1016/j.diabres.2012.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life gains among people with type 1 diabetes participating in the Dose Adjustment for Normal Eating (DAFNE) structured education programme

Abstract: Aims: To examine predictors of quality of life gains among people with type 1 diabetes following DAFNE (Dose Adjustment for Normal Eating) self-management training programme.Methods: Clinical and questionnaire data were collected from 437 patients from 6 hospital centres before, and at 18 month post, DAFNE intervention. Glycated haemoglobin (HbA 1c ), weight and height, and blood pressure levels were recorded by clinicians during clinic appointments. Questionnaires included the Diabetes-Specific Quality of Lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…International data have shown that depressive symptoms are a significant predictor of satisfaction with QOL in youth with T1D (Byrne et al . ). There was no significant relationship between depressive symptoms and HbA1c in this study as well as our cross‐sectional analysis, which was consistent with a study conducted in mainland China (Wang et al .…”
Section: Discussionmentioning
confidence: 97%
“…International data have shown that depressive symptoms are a significant predictor of satisfaction with QOL in youth with T1D (Byrne et al . ). There was no significant relationship between depressive symptoms and HbA1c in this study as well as our cross‐sectional analysis, which was consistent with a study conducted in mainland China (Wang et al .…”
Section: Discussionmentioning
confidence: 97%
“…HRQoL has been widely studied in people with type 1 diabetes, generally in relation to other aspects such as the presence of chronic complications (DCCT Research Group, 1996; Hahl et al, 2002; Jacobson et al, 2013), glycemic control (Hoey et al, 2001; Tan et al, 2005; Cooke et al, 2015; Stahl-Pehe et al, 2017), disease duration (Sparring et al, 2013) and the impact of structured education programs (Speight et al, 2010; Byrne et al, 2012). The question of how to assess the burden of treatment and its effect on HRQoL in patients with type 1 diabetes has received less attention to date.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have documented positive impacts of various DSMPs on outcomes such as: glycated hemoglobin and fasting blood glucose levels [57]; rates of hospitalization [8]; lifestyle outcomes [9] and quality of life [10]. Other studies found no significant improvements in clinical outcomes [1113] or quality of life [7].…”
Section: Introductionmentioning
confidence: 99%